MYOC Mutations in Black South African Patients with Primary Open-angle Glaucoma: Genetic Testing and Cascade Screening. (March 2015) - Williams, Susan Eileen Isabella; Carmichael, Trevor Robin; Wainstein, Tasha; Hobbs, Angela; Ramsay, Michele
Abstract Background: Primary Open Angle Glaucoma (POAG) is an important cause of irreversible blindness in South Africa. Mutations in the MYOC gene are important in monogenic POAG. This study aimed to characterize potentially pathogenic MYOC mutations in this population. Materials and Methods: Self-identified black South African POAG patients (215) and unaffected control participants (214) had ophthalmological examinations and DNA extraction. Potentially pathogenic MYOC variants were genotyped in the study population. Family members of participants with the mutations were screened for glaucoma clinically and for the mutations using Sanger sequencing. Results: The following mutations were genotyped: Gly374Val (2 POAG patients), Lys500Arg (3 POAG patients) and Tyr453del (5 POAG patients). None of the relatives screened for Gly374Val had the mutation or POAG. The Lys500Arg mutation did not co-segregate with the disease in an affected family. The Tyr453del mutation co-segregated with the disease, but demonstrated incomplete penetrance. POAG patients with the Tyr453del mutation had adult-onset POAG with high intraocular pressures and advanced cupping. Conclusions: Overall, 3.3% of black South Africans with POAG have a Gly374Val or Tyr453del MYOC mutation. The Tyr453del mutation is incompletely penetrant. That the mutation is necessary but insufficient introduces a counseling dilemma. Mutation screening can, however, identify high-risk individuals who can be monitored to detect early signs of the disease. The Gly374Val mutation is predicted to be damaging to MYOC. The Lys500Arg mutation is predicted to be benign and tolerated. This study has important implications for the management and counseling of black South African patients with POAG and their families.